Pengaruh Pengeluaran Pemerintah, Pengangguran, dan Inflasi terhadap Kemiskinan di Provinsi Sumatera Utara Tahun 2001–2023 - Siahaan, Tegar Efraim G.; Suharianto, Joko; Hasibuan, Alawi Parlindungan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the effect of government spending, unemployment, and inflation on the number of poor people in North Sumatra Province during the period 2001-2023. The data used is secondary data obtained from the Central Bureau of Statistics (BPS) and Bank Indonesia. The analysis method used is multiple linear regression with EViews 13 software. The classical assumption tests used include normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results show that government spending has a negative and significant effect on poverty, while unemployment and inflation have no significant effect. Simultaneously, the three variables have a significant influence on the number of poor people in North Sumatra. It is recommended that the government increase the effectiveness of spending on strategic sectors for poverty alleviation and maintain economic stability with integrated policies.